Use of Hantzsch reaction for quantitation of milnacipran as a magic treatment for fibromyalgia syndrome in human plasma and urine. (9th August 2020) - Mostafa, Islam M.; Omar, Mahmoud A.; Nagy, Dalia M.; Derayea, Sayed M.
Abstract: A new fluorimetric procedure is described for analysis of milnacipran in its bulk, tablet dosage forms, as well as in biological human samples such as plasma and urine. The suggested method relies on the construction of a derivative with strong fluorescence called dihydropyridine derivative. This derivative resulted from the interaction of the primary amino group in the studied drug and acetylacetone/formaldehyde in McIlvaine buffer (pH 5). The fluorescent dihydropyridine derivative was measured at 470 nm. Influences of experimental variables namely pH, reagent concentration and temperature were examined and optimized. The calibration curve showed linearity over the range of 0.15–1.25 μg ml −1 of milnacipran with an R 2 value of 0.9998. The detection limit was 0.02 μg ml −1 and the determination limit was 0.07 μg ml −1 . The developed procedure was successfully used in the assay of the studied drug in Avermilan® tablets with excellent selectivity. In addition, the reaction was applied to estimate the drug in spiked human plasma and urine with mean percentage recoveries of 100.04 ± 1.61 and 99.78 ± 0.81% for urine and plasma, respectively. Abstract : In this work, Hantzsch reaction was used for assay of milnacipran (MCP) in pure form, tablets dosage form and biological fluids. The developed method is sensitive, reproducible, selective and cheap. Under the optimized experimental conditions the analysis can be carried out over the concentration range of 0.15‐1.25 μg mL ‐1 . The suggested methodology was based on condensing the primary amino group of MCP with acetylacetone/formaldehyde to form a dihydropyridine derivative that having high fluorescence.